LKPD Bentuk Molekul Berbasis Inkuiri Terstruktur Dengan Menggunakan Pemodelan Tiga Dimensi - Nurafni Nurafni; Minda Azhar (Universitas Negeri Padang, 2019)
This study is research and development (R and D) and using 4-D models, but disseminate step is not done. Validation of student worksheets has been done by chemistry lecturers and chemistry teachers. The practicality of student worksheets has been done by chemistry teachers and students of 2nd grade of SMAN 1 Pariaman. The result showed that moment kappa average of validity was 0,83 with very high validity category and moment kappa average of practicality were 0,9 by chemistry teachers and 0,86 by students with very high category. Therefore student worksheets of molecular shape based on structured inquiry with emphasis on the submicroscopic level using 3-D models is valid and practice to be used on the chemistry learning.